2007
DOI: 10.1128/mcb.00770-06
|View full text |Cite
|
Sign up to set email alerts
|

DNA Recombination-Initiation Plays a Role in the Extremely Biased Inheritance of Yeast [rho] Mitochondrial DNA That Contains the Replication Origin ori5

Abstract: Hypersuppressiveness, as observed inEukaryotic cells gain most of the energy required for cellular functions by oxidative respiration in mitochondria. These organelles contain hundreds to thousands of copies of a mitochondrial DNA (mtDNA) genome that encodes components essential for respiration and protein synthesis. Generally, mitochondrial alleles segregate during vegetative cell growth (vegetative segregation), and all copies of mtDNA within a cell or an individual generally have the same sequence (homoplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
112
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(114 citation statements)
references
References 59 publications
2
112
0
Order By: Relevance
“…Mutation in MHR1 reduces concatemer formation, which subsequently affects the partitioning of newly synthesized mtDNA into the buds and delays the establishment of mtDNA homoplasmy in the daughter cells (200,201). Mhr1 is also required for the replicative advantage of the ori5 hypersuppressive Ϫ genome, which has apparently frequent double-strand breaks (202), consistent with its role in recombinational repair of mtDNA. It was initially proposed that Mhr1 may have a Rad52-type activity like Red␤ in the phage .…”
Section: Linking Mtdna Recombination Repair and Replicationmentioning
confidence: 88%
“…Mutation in MHR1 reduces concatemer formation, which subsequently affects the partitioning of newly synthesized mtDNA into the buds and delays the establishment of mtDNA homoplasmy in the daughter cells (200,201). Mhr1 is also required for the replicative advantage of the ori5 hypersuppressive Ϫ genome, which has apparently frequent double-strand breaks (202), consistent with its role in recombinational repair of mtDNA. It was initially proposed that Mhr1 may have a Rad52-type activity like Red␤ in the phage .…”
Section: Linking Mtdna Recombination Repair and Replicationmentioning
confidence: 88%
“…The severe reduction of Gcf1p levels in C. albicans mitochondria under repressed conditions apparently leads to the observed decrease in recombination structures that could be used for initiation of mtDNA replication. Recently, it has been demonstrated that in yeast recombination is linked to the initiation of mtDNA replication (Ling et al, 2007;J. M. Gerhold and others, unpublished results).…”
Section: Construction Of a C Albicans Strain With A Conditional Allementioning
confidence: 99%
“…5). We and others have previously discussed the universal impact of RDR in organelle DNA maintenance with examples from yeasts, plants, and human heart (7,(51)(52)(53)(54)(55)(56). A link between topology and maintenance mechanisms has been drawn for chloroplast DNA (54), and this concept applies for C. albicans mtDNA as well.…”
Section: Discussionmentioning
confidence: 99%